Analisis Hasil Rapor Mutu Pendidikan untuk Kesiapan Sekolah dalam Pelaksanaan ANBK pada Sekolah SDN Wadas III Karawang (Jurnal Sekolah Dasar, 2025)
From the results of the quality report analysis at SDN Wadas III School, it shows that in 2022, the results of the quality report for the literacy competency assessment will have a value above the minimum competency of 2.33, a similar unit value for National Education is 1.75, the average score for the city district is 1.62, the provincial average 1.74, national average value 1.71, for numeracy students are in the category above minimum competency 2.17, unit value is similar to National Education 1.59, city district average score 1.53, provincial average score 1.6, national average score 1.57, in 2023, the results of quality report cards for literacy competency assessments will decrease by 3.33% with the achievement of most students having reaching the minimum competency limit for reading literacy. For numeracy, it increased by 3.70% d with the achievement of students having reached the minimum competency limit for numeracy. The results of school quality report cards decreased for literacy and increased for numeracy. The purpose of this research is to find out the results of the education quality report before and after the implementation of ANBK, to find out the readiness of schools in implementing ANBK activities, to find out the obstacles and efforts faced in implementing ANBK activities. This research method uses descriptive quantitative research. Quantitative descriptive research is research that describes variables as they are, supported by data in the form of numbers produced from actual conditions. This research uses data collection techniques through questionnaires, observations and interviews. Based on the results of the research conducted, it is known that the 2024 ANBK Literacy and Numerization Results seen from the Education Quality Report Card at SDN Wadas III Elementary School increased by 3.33% for literacy competency and 6.67% for numerization competency. School preparation in facing the implementation of the National Based Assessment The computers are quite ready, the Implementation of the Computer Based National Assessment (ANBK) at Wadas III Public Elementary School is running well, orderly and smoothly, the obstacles that arise encountered during the implementation of the National Assessment can be resolved quickly and precisely.